Trachomitum venetum (L.) Woodson subsp. sarmatiense (Woodson) Avetisjan (Apocynaceae) у Приазов’ї - Коломійчук, В.П. (Український ботанічний журнал, 2013)
Приводятся современные местонахождения редкого дизъюнктивного таксона Trachomitum venetum subsp. sarmatiense в Приазовье. Дана ценотическая характеристика выявленных автором местонахождений. Data on current localities of a rare disjunctive taxon, Trachomitum venetum subsp. sarmatiense, in the Sea of Azov region are presented. Coenotic characteristics of the species localities are given.